Elucidation of acid strength effect on ibuprofen adsorption and release by aluminated mesoporous silica nanoparticles. Issue 38 (30th March 2015) - Kamarudin, N. H. N.; Jalil, A. A.; Triwahyono, S.; Sazegar, M. R.; Hamdan, S.; Baba, S.; Ahmad, A.
Abstract : Mesoporous silica nanoparticles (MSN) with 1–10 wt% loading of aluminum (Al) were prepared and characterized by XRD, N2 physisorption, 29 Si and 27 Al NMR, FT-IR and FT-IR preadsorbed pyridine. Abstract : Mesoporous silica nanoparticles (MSN) with 1–10 wt% loading of aluminum (Al) were prepared and characterized by XRD, N2 physisorption, 29 Si and 27 Al NMR, FT-IR and FT-IR preadsorbed pyridine. All samples were evaluated for ibuprofen adsorption and release. The results showed that MSN gave almost complete ibuprofen adsorption while the addition of 1, 5, and 10 wt% Al onto MSN (1Al-MSN, 5Al-MSN and 10Al-MSN) resulted in 35%, 58%, and 79% of adsorption, respectively. The characterization results elucidated that the highest adsorptivity of MSN was due to its highest surface silanol groups, while the increase in Brönsted acidity upon loading of Al provided more adsorption sites for the higher activity. Regardless of its highest adsorption capacity, MSN demonstrated the highest and fastest release (∼100%) in 10 h, followed by 1Al-MSN, 5Al-MSN and 10Al-MSN. The increase in Al loading increased the acid sites that hold the ibuprofen molecules, which raised the retention in ibuprofen release. The p K a of Si–OH–Al that is lower than Si–OH sites also attracted the ibuprofen more strongly, which resulted in the slower release of Al-MSN as compared to MSN. The cytotoxicity study exhibited that ibuprofen loaded Al-MSN was able to reduce the toxicity in the WRL-68 cells, verifying its ability to hold and slow the release of ibuprofen as well as minimize the risk of drug overdose.